Seed removal by ants from faeces produced by different vertebrate species - Pizo, M. A.; Guimaraes, P. R.; Oliveira, P. S. (Universite Laval, 2005)
Ants frequently harvest seeds from faeces of frugivorous vertebrates. By transporting these seeds to nests, ants may influence seed dispersal success of plants. Seed removal by ants from vertebrate faeces is influenced by the seed species involved. Faeces from different vertebrates differ in chemical composition and physical characteristics. It remains unclear, however, whether the faeces itself affects the ant-seed interaction. In this study experimental seed-containing faecal portions were prepared using defecations of birds, marsupials, and monkeys and seeds of two aroids (Philodendron corcovadense and P. ppendiculatum, Araceae) and one liana species (Schlegelia parviflora, Bignoniaceae). Faecal portions were arranged along a transect established in the understory of a lowland rainforest in southeast Brazil. For P. appendiculatum the probability of detection and the proportion of seeds removed were identical between marsupial and monkey faeces. For P. corcovadense and S. parviflora, the probability of detection was affected by seed species and, apparently, also by the interaction between seed species and type of faeces (P = 0.097), but not by the type of faeces itself (bird or monkey). Both factors (i.e., seed species and type of faeces) affected the proportion of seeds removed (faeces type was marginally significant; P = 0.08), whereas the interaction between them was not significant. The results indicate that seed species affects seed removal by ants, while the type of faeces probably interacts with seed traits to influence faeces detection.
Keywords: ants; Mata Atlantica; secondary seed dispersal